2021
DOI: 10.14336/ad.2021.0325
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastic Effect of Exercise Through Astrocytes Activation and Cellular Crosstalk

Abstract: Physical exercise is an effective therapy for neurorehabilitation. Exercise has been shown to induce remodeling and proliferation of astrocyte. Astrocytes potentially affect the recruitment and function of neurons; they could intensify responses of neurons and bring more neurons for the process of neuroplasticity. Interactions between astrocytes, microglia and neurons modulate neuroplasticity and, subsequently, neural circuit function. These cellular interactions promote the number and function of synapses, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 148 publications
0
24
0
Order By: Relevance
“…, 46-48]. Patients with AD dementia show improvements in memory and cognitive behavior when they start exercising regularly [ 8 - 15 , 18 , 49 ]. This study provides evidence for the beneficial effect of voluntary running on spatial memory and its underlying mechanisms in 3xTg-AD mice.…”
Section: Discussionmentioning
confidence: 99%
“…, 46-48]. Patients with AD dementia show improvements in memory and cognitive behavior when they start exercising regularly [ 8 - 15 , 18 , 49 ]. This study provides evidence for the beneficial effect of voluntary running on spatial memory and its underlying mechanisms in 3xTg-AD mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies have shown that the changes in astrocytes may be a key mechanism accounting for the improvement of cognitive and executive functions related to exercise ( Li et al, 2021 ; Maugeri et al, 2021 ). Astrocytes are the main homeostasis and defense elements of the brain, helping to maintain cognitive reserve through a variety of mechanisms ( Verkhratsky et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have shown that astrocytes may be the perspective targets of exercise mimetics ( Lalo and Pankratov, 2021 ). In general, astrocytes are the central components for physical exercise-induced cognitive improvement in many neurodegenerative and neurovascular diseases ( Li et al, 2021 ). The modulation of astrocytes polarization from neurotoxic A1 to neuroprotective A2 phenotypes may be an important mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that masticatory exercise improves cognitive function in older adults [ 17 ] and thus the link between cognitive decline and masticatory dysfunction is now clear [ 8 , 18 , 19 , 20 , 21 , 22 ]. As loss of masticatory activity [ 8 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 ] and sedentary life style [ 23 , 24 ] are risk factors for age-related cognitive decline, there is a need to focus attention on those sub-populations that experience greater oral health deterioration or impairment of the stomatognathic system, and those having living sedentary lives.…”
Section: Introductionmentioning
confidence: 99%
“…As a function of environmental stimuli [ 41 , 42 ], age [ 43 , 44 ], or the presence of other pathology [ 45 , 46 , 47 ], astrocytes differentially respond to changes in the microenvironment of the brain, in both form and function [ 48 , 49 ]. For example, physical exercise induces astrocyte proliferation and morphological changes, which alters the interplay between astrocytes, microglia and neurons to enhance neuroplasticity [ 23 , 50 , 51 , 52 ]. A distinctive pattern of gene expression is also induced in regions of the brain that are activated by exercise [ 53 ].…”
Section: Introductionmentioning
confidence: 99%